Respuesta :
Step-by-step explanation:
Substitute the value of y into the equation;
[tex]8x-2(4)=48[/tex]
Find the value of x.
Multiply;
[tex]8x-8=48[/tex]
Add 8 to each side;
[tex]8x=56[/tex]
Divide each side by 8;
[tex]x=7[/tex]
Answer:
x = 7
Step-by-step explanation:
Given:
- y = 4
Step-1: Substitute the y-variable in the equation (8x – 2y = 48)
- ⇒ 8x - 2y = 48
- ⇒ 8x - 2(4) = 48
Step-2: Simplify the L.H.S
- ⇒ 8x - 2(4) = 48
- ⇒ 8x - 8 = 48
Step-3: Add 8 both sides
- ⇒ 8x - 8 = 48
- ⇒ 8x - 8 + 8 = 48 + 8
- ⇒ 8x = 56
Step-4: Divide 8 both sides
- ⇒ 8x = 56
- ⇒ 8x/8 = 56/8
- ⇒ x = 7